Evaluation of the Nutritive values of solid heavy phase in replace corn in broilers diet - A P Sinurat; T Purwadaria; I AK Bintang; T Pasaribu (Jurnal Ilmu Ternak dan Veteriner, 2006)
Indonesia is still importing corn for feed. Utilization of nonconventional feedstuffs may reduce this importation. One of them is solid heavy phase (SHP), i.e., a solid substance gained after filtration of liquid waste of crude palm oil factory with a potential production approximately 2 million ton/year. This research was carried out to study the utilization of SHP to replace corn in broiler’s diet. The SHP was dried and analysed for its nutrient compositions. The metabolisable energy was measured by using hens. Feeding trial was then conducted by replacing corn with SHP in various levels, i.e., 0 (Control), 10, 20, 30, and 40%. All diets were formulated to be isocalori dan isonitrogen. Five hundred broilers DOC were used in this trial and fed for 5 weeks. The performances of the birds were obsereved as parameters. Results showed that the ash, minerals crude fibre and fat contents of the SHP were higher than the corn. The crude protein of the  SHP was similar to that of corn, but some amino acids content of the SHP were lower than the corn. The AME and TME values of SHP were 3271 and 3465 cal/g, respectively. Results of feeding trial showed that body weight of the birds were less as the level of SHP to replace corn increased in the diet. The FCR also showed impared as the levels of SHP increased in the diet. However, replacement of 10% corn with SHP did not significantly affect the body weight and FCR as compared with the control. Feed consumptions of the birds were not significantly affected by replacing corn with SHP. Carcass yield and relative weights of some internal organs were not significantly different between dietary treatments. It is concluded that the solid heavy phase could be used to replace 10% corn in broiler’s diet.Key Words: Solid Heavy Phase, Palm Oil By Products, Broilers